2016
DOI: 10.1016/j.fertnstert.2016.07.290
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results for aneuploidy screening in south Asian women compared to caucasians undergoing PGS

Abstract: A total of 39,643 cycles by 22,668 patients were available for analysis. Mean age for each minority group was higher than Caucasians. Mean BMI was higher for African Americans and lower for Asians. African Americans were more likely to be diagnosed with diminished ovarian reserve, tubal and uterine factors, and less likely to be diagnosed with endometriosis, male factor, or ovulatory dysfunction, and asians were more likely to be diagnosed with diminished ovarian reserve (P<0.0001 for each). The number of embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…The average number of blastocysts analyzed for both the ethnic populations was also similar which was in contradiction with the previous findings by Sharara et al ., where they have concluded that South Asian women produced fewer blastocysts for biopsy, had a lower number of top-quality embryos, resulting in a lower clinical pregnancy rate compared to Caucasian women. [11] However, in the current study, we have observed that for TE biopsy, patients had an equal chance of having at least one euploid embryo available for transfer in both the ethnic groups (75.3% vs. 75%, respectively, for Spanish vs. Indian population). While in cleavage stage biopsy group, Indian patients had very high chance of having at least one euploid embryo available for transfer compared to Spanish population (70.5 vs. 49.5, respectively), which may be due to a very small number of patients in Indian group compared to Spanish group (6677 vs. 288, respectively).…”
Section: Discussioncontrasting
confidence: 49%
“…The average number of blastocysts analyzed for both the ethnic populations was also similar which was in contradiction with the previous findings by Sharara et al ., where they have concluded that South Asian women produced fewer blastocysts for biopsy, had a lower number of top-quality embryos, resulting in a lower clinical pregnancy rate compared to Caucasian women. [11] However, in the current study, we have observed that for TE biopsy, patients had an equal chance of having at least one euploid embryo available for transfer in both the ethnic groups (75.3% vs. 75%, respectively, for Spanish vs. Indian population). While in cleavage stage biopsy group, Indian patients had very high chance of having at least one euploid embryo available for transfer compared to Spanish population (70.5 vs. 49.5, respectively), which may be due to a very small number of patients in Indian group compared to Spanish group (6677 vs. 288, respectively).…”
Section: Discussioncontrasting
confidence: 49%